The Leica M photographer : photographing with Leica's legendary rangefinder cameras - Solcher, Bertram (Rocky Nook, Inc., 2015)
What it is and what it isn't. This not a camera manual for the Leica M, nor is it a book that will teach you photography. Nevertheless, in Bertram Solcher's book you will learn a whole lot about your camera and how to use it, and about the art and craft of photography. This book contains a collection of illustrated essays that are meant to reveal the secrets of working with a rangefinder camera. To be more precise, with the best camera ever made. The book's ultimate goal is to ignite your passion for the kind of spontaneous, minimalist, and creative photography we admire in the works of Hen.